LEXICAL-SEMANTIC FEATURES OF WORDS AND TERMS RELATED TO HORSE BREEDING IN KABARDIN-CIRCASSIAN LANGUAGE - Z. G. KHUTEZHEV; R. S. TLUPOVA (Кавказология, 2020)
The article examines one of the active strata (groups) of Adyghe vocabulary, consisting of words and terms related to horse breeding. Here, for the first time, the lexical and semantic features of words included in the specified lexical layer are studied. A classification is proposed, in accordance with which eight semantic groups of words are distinguished related to horse and horse breeding: 1) tokens that name parts of the horse's body; 2) tokens naming the age of the animal; 3) tokens that name a horse in accordance with its purpose and the specifics of the work performed (for example, a draft horse); 4) the names of customs, rituals and festivities organized with the direct participation of the horse; 5) the naming of people associated with the horse, its breeding; 6) names of horse diseases; 7) the names of the elements of horse harness and other items related to the care of the horse; 8) the names of the horses in accordance with the ability to reproduce offspring. The article also provides typology of lexemes related to horse breeding, according to their substantive features, activity / deactivation criteria in the modern Kabardino-Circassian language, originality / borrowing, style characteristics, etc. In accordance with the indicated criteria, outdated vocabulary (archaisms, historicisms), ethnonyms, mythologisms, dialectisms, special (professional) vocabulary, borrowings, vernacular, etc. In the study of lexemes, the ethnography of the material in question is taken into account, interpretations of words and terms are given, reasoned by illustrative material. The role and place of the studied stratum in common Adyghe vocabulary is determined, lexical-grammatical and lexical-semantic features of some words and terms related to horse breeding are revealed. The results of the study can be useful to scientists, teachers of higher and secondary educational institutions, as well as students, undergraduates and graduate students when writing qualification and other types of work.